ANALYSIS OF THE APPLICATION OF COOPERATION AND IMPROVEMENT OF STORYTELLING SKILLS IN LEARNING ELEMNETARY SCHOOL STUDENTS - Dian Sindi Nofianti; Kartika Chrysti Suryandari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this study is to describe cooperation and storytelling skills in students in learning.This research is a qualitative descriptive study with observation techniques and questionnaire distribution with sample schools of SD Negeri 5 Panjer Kebumen in 2018/2019 academic year.The results of this study indicate: (1) the application of cooperation in learning causes positive dependence, increases sense of responsibility, facilitates communication, and fosters mutual respect. (2) by improving the ability to tell stories can improve skills in using grammar, accuracy of words and sentences, and fluency in conveying sentences.The conclusion with the application of cooperation in learning can improve storytelling skills.